2012
DOI: 10.1002/pmic.201200016
|View full text |Cite
|
Sign up to set email alerts
|

LCMS‐based serum metabolic profiling for genitourinary cancer classification and cancer type‐specific biomarker discovery

Abstract: Bladder cancer (BC) and kidney cancer (KC) are the first two commonly occurring genitourinary cancers in China. In this study, a comprehensive LC-MS-based method, which utilizes both reversed phase liquid chromatography (RPLC) and hydrophilic interaction chromatography (HILIC) separations, has been carried out in conjunction with multivariate data analysis to discriminate the global serum profiles of BC, KC, and noncancer controls. An independent test set consisting of different patients has been used to objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 32 publications
2
64
0
Order By: Relevance
“…fact that tumor cells utilize enhanced β-oxidation of fatty acids which are the skeleton of TG for rapid growth. Similar to these results, Lin et al [12] found that patients with bladder cancer have enhanced level of phosphatidylcholine. In another study [13], canine bladder cancer tissue sections and adjacent normal tissues were imaged using desorption electrospray ionization (DESI) mass spectrometry and both glycerophospholipid and sphingolipid profiles between the tissue types differed, both in the intensities of the lipid signals present and the pattern of the lipid signals.…”
Section: Introductionsupporting
confidence: 74%
“…fact that tumor cells utilize enhanced β-oxidation of fatty acids which are the skeleton of TG for rapid growth. Similar to these results, Lin et al [12] found that patients with bladder cancer have enhanced level of phosphatidylcholine. In another study [13], canine bladder cancer tissue sections and adjacent normal tissues were imaged using desorption electrospray ionization (DESI) mass spectrometry and both glycerophospholipid and sphingolipid profiles between the tissue types differed, both in the intensities of the lipid signals present and the pattern of the lipid signals.…”
Section: Introductionsupporting
confidence: 74%
“…Determining the relative abundance of metabolites with MS-based techniques has been successfully applied to discover potential metabolic biomarkers of various human diseases. 21-24 …”
Section: Introductionmentioning
confidence: 99%
“…However, a C17 sphinganine has been detected in human plasma as a biomarker of kidney cancer. 40 The role of sphingolipid bases in HIV infection is currently unknown, but sphingolipids and their metabolites can initiate cellular apoptosis 41 , regulate HIV viral entry into cells 42,43 and are associated with age-related changes in cholesterol/low density lipoprotein levels. 44 Concentrations of a tetrapeptide increased in patients on atazanavir, possibly as a result of TDF and reduced proximal tubular function and reduced re-uptake of low molecular weight proteins.…”
Section: Variation In the Endogenous Metabolome As A Results Of Cartmentioning
confidence: 99%